The Impact of Strategic Planning on Marketing Performance: a critical review - Ruiz-Andrade, José G.; Solís-Palafox, Claudia L.; López-Luna, Norma A. (EFIM Ediciones, 2021)
The changing environment in which organizations are immersed today, leads them to make informed strategic decisions, which is why marketing managers need to constantly practice the formalization, implementation and evaluation of strategic marketing plans. Previous literature supports the importance of this planning in the results of organizations, however there are some barriers that have to do with culture and policies, for example, confidence in planning and its results, resistance to change and cognitive barriers that have to do with lack of knowledge, skills and innovation. This is why a critical approach to the incidence of strategic planning on marketing performance is planned through a literature review. The results point out that the relationship between strategic marketing planning and the impact it generates within companies when put into practice has positive results in performance; however, a high level of knowledge of the environment is required for planning to be effective with respect to results.